Aquatic and Marine Ecosystems - Deborah J. Glauer (EDIS)
The new Florida 4-H Aquatic/Marine Ecosystems Leader’s Guide, is a part of the Environmental Education Framework, OUR NATURAL WORLD, This framework includes the basic premise that aquatic/marine environments are important in children’s lives, particularly to those children in Florida. The 4-H Aquatic/Marine Ecosystems program provides an opportunity for young people to practice a variety of life skills while learning subject matter.